Developing Professional Motivation in Higher Education: A Mixed-Method Investigation of Psychological and Institutional Factors - Ayakulov Ulug‘bek Abdug‘affor o‘g‘li (European International Journal of Pedagogics, 2026)
This study investigates the psychological and pedagogical factors shaping professional motivation among university students using a mixed-method research design integrating quantitative and qualitative approaches. The sample consisted of 278 undergraduate students, and data were collected through standardized questionnaires and semi-structured interviews. Statistical analysis revealed that intrinsic motivation, professional identity, and perceived competence are the primary determinants of professional motivation, explaining 48% of its variance. Extrinsic motivation was found to function as a supplementary, short-term incentive rather than a stable predictor. The findings confirm the theoretical assumptions of Self-Determination Theory and extend previous local studies by empirically modeling the structural relationships between motivational components. An integrative conceptual model of professional motivation is proposed, demonstrating that sustainable professional motivation is grounded in internalized interest, identity formation, and competence perception. The results provide both theoretical and practical implications for enhancing motivational environments in higher education and improving students’ professional development outcomes.